2014
DOI: 10.1589/jpts.26.475
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pilates Mat and Apparatus Exercises on Pain and Balance of Businesswomen with Chronic Low Back Pain

Abstract: [Purpose] The purpose of this study was to examine the influence of mat Pilates and apparatus Pilates on pain and static balance of businesswomen with chronic back pain. [Subjects and Methods] Participants were randomly allocated to Pilates mat exercises (PME) or Pilates apparatus exercise (PAE), and performed the appropriate Pilates exercises 3 days per week for 8 weeks. In order to measure the improvement in the participants’ static balance ability as a result of the exercise, the sway length and sway veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 17 publications
0
24
0
5
Order By: Relevance
“…For businesswomen doing 8 weeks of Pilates exercise, the article showed that subjects had better balance with mat-Pilates exercise than with Pilates apparatus exercise, and were better able to reduce CLBP. Although these 2 results seem to contradict each other, they did not investigate nonspecific CLBP RMDQ, and the VAS mean differences did not achieve MCID31 ) . Lee et al also did not report whether there was supervision for Pilates therapy.…”
Section: Discussionmentioning
confidence: 90%
“…For businesswomen doing 8 weeks of Pilates exercise, the article showed that subjects had better balance with mat-Pilates exercise than with Pilates apparatus exercise, and were better able to reduce CLBP. Although these 2 results seem to contradict each other, they did not investigate nonspecific CLBP RMDQ, and the VAS mean differences did not achieve MCID31 ) . Lee et al also did not report whether there was supervision for Pilates therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Mat-based Pilates exercises require more core strength than equipment-based exercises (Lee et al, 2014), and thus may not be an optimal choice for an injured, deconditioned worker. Instruction from a certified Pilates instructor or physical therapist and following a protocol that focuses on the individual's injury and/or chronic condition enhances the usefulness and effectiveness of Pilates in a healthcare setting (Donzelli et al, 2006;da Luz et al, 2014;Natour et al, 2015;Wajsweiner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pilates exercise has been introduced17,18,19,20,21,22,23 ) . Pilates exercise is also called Contrology and it is based on the idea of muscle control.…”
Section: Introductionmentioning
confidence: 99%
“…It focuses to make a neutral spine of body to prevent excess flexion and extension of the spine when walking upright17, 18 ) . Since Pilates exercise has been shown to have positive effects on development of muscular strength and endurance and improvement of flexibility, it has been used not only for exercise programs for healthy adults but also for rehabilitation for the elderly19, 21 ) . Moreover, unlike other exercise programs, Pilates exercise can be performed with various tools to adjust the fitness level for the elderly, who have weaker physical strength and it can be performed at home without having to visit a rehabilitation center22, 23 ) .…”
Section: Introductionmentioning
confidence: 99%